The effect of a training program using kinetic stories on developing motor creativity in intellectually disabled children capable of learning - Yaakoubi, fateh (sports creativity, 2025)
The research aimed to study a training program using movement stories to develop motor creativity in intellectually disabled children capable of learning, specifically in developing certain motor creativity abilities such as motor fluency, motor flexibility, and motor originality. The study included 18 students who were purposefully selected and divided into two equal groups: 9 students in the experimental group and 9 students in the control group. The training program lasted 8 weeks, during which 40 games were allocated to each program, distributed across 5 educational units per week.